Model Simulasi Emisi dan Penyerapan CO2 di Kota Bogor - Rizka Permatayakti Rasyidta Nur; Herry Purnomo (Institut Pertanian Bogor, 2015)
Most of the urban pollution is the result of carbon dioxide (CO2) emission from human activities. This research identified CO2 emission and absorption in Bogor, and also the alternatives to solve the emission problem by system model and simulation. CO2 emission and absorption system model was created using software Stella 9.0.2 based on loss-gain emission concept for 30 years prediction. Human activities that contribute to CO2 emission are transportation, industries, energy consumption such as fuel or electricity, house hold waste, and farms, while the decrease factor is green open spaces as CO2 sequester. The alternatives to solve emission problem in Bogor is created based on green city concept by including the environmental aspects in every urban activity. The result of this research, the CO2 emission of Bogor reached 20.027.878 tons and the absorption reached 93.843 tons in 2042. Combined mitigation alternatives in several sectors could reduce CO2 emission by 2.797.667 tons in 2042 and CO2 emission could be neutralized by reforestation in 2036.